2009
DOI: 10.1097/ccm.0b013e31819573a5
|View full text |Cite
|
Sign up to set email alerts
|

Interactive video instruction improves the quality of dispatcher-assisted chest compression-only cardiopulmonary resuscitation in simulated cardiac arrests*

Abstract: The addition of interactive video communication to dispatcher-assisted chest compression-only CPR initially delayed the commencement of chest compressions, but subsequently improved the depth and rate of compressions. The benefit was achieved mainly through real-time feedback.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
1
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 33 publications
3
51
1
4
Order By: Relevance
“…In addition, only 18-20% of the subjects performed chest compressions to the recommended depth. In the study by Yang et al, 2 the mean chest compression depth was 36 mm, and 20% of the subjects performed chest compression to the recommended depth, similar to the results of this study. In our study, most CPR performances that did not meet the recommended depth showed that it was due to shallow compressions.…”
Section: Audio Instructions Video Instructions P-valuesupporting
confidence: 90%
See 4 more Smart Citations
“…In addition, only 18-20% of the subjects performed chest compressions to the recommended depth. In the study by Yang et al, 2 the mean chest compression depth was 36 mm, and 20% of the subjects performed chest compression to the recommended depth, similar to the results of this study. In our study, most CPR performances that did not meet the recommended depth showed that it was due to shallow compressions.…”
Section: Audio Instructions Video Instructions P-valuesupporting
confidence: 90%
“…The results obtained are similar to those from this study, but the rate of chest compressions from a previous study was slightly slower. 2 It is presumed that if the subjects were informed of their chest compression rate of 100 min −1 by phone, or if the chest compression rate was corrected through mobile video telephony, it would have been easier for them to maintain the appropriate chest compression rate while watching the CPR video, as was shown in this study.…”
Section: Audio Instructions Video Instructions P-valuementioning
confidence: 79%
See 3 more Smart Citations